Experimental and theoretical investigation of tension stiffening and curvature in RC beams with extended concrete cover - Sokolov, Aleksandr; Valiukas, Domas; Praliyeva, Mariyam; Kumar, Amarjeet; Bacinskas, Darius; Kaklauskas, Gintaris (Journal of Civil Engineering and Management, 2025)
Accurate assessment of tension stiffening is important for predicting deflection and crack width in RC structures. Earlier studies by the authors have shown that an extended cover thickness increases tension stiffening in bending RC members. The current study experimentally and theoretically investigates curvature and tension stiffening in RC beams nominally having a 50 mm cover for 32 mm bars of tensile reinforcement. The four-point bending tests were carried out on square section (400×400 mm) RC beams. Mean experimental curvatures were obtained for the pure bending zone by different approaches, namely, from a mid-point deflection and from strains at several horizontal layers measured either by LVDT or DIC technique. The tension stiffening effect in the test beams was quantified by inversely calculating the resultant internal force of tensile concrete, Nct, using the test moment – curvature diagrams. Tension stiffening is characterized by parameter β0 indicating the ratio of β0 = M / Mcr at which the force Nct reaches zero. The condition Nct = 0 represents the bending stiffness of a fully cracked RC section. Earlier studies by the authors have shown that parameter β0 equals to 3 for the beams with a typical cover thickness (25–35 mm). The current study has demonstrated that for the beams having nominal cover thickness of 50 mm and bar diameter of 32 mm, parameter β0 reached rather high values indicating a little degradation of tension stiffening with increasing load.